Ashok Vajpeyi ka Rachna Sansar: Ek Vishleshanatmak Adhyayan: The Creative World of Ashok Vajpeyi: An Analytical Study - Dr. Abha Gupta (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2025)
Ashok Vajpeyi is regarded as one of the leading poets of modern Hindi literature. His poetry expresses the complexities of contemporary life and human experiences with depth and sensitivity. Themes such as love, hope toward life, and the human will to survive and continue are strongly reflected in his poems. Critics often view him as a poet who strives to preserve human sensitivity and faith even during difficult times. The social and cultural environment in which he wrote was marked by many crises and transformations. During that period, issues such as social disintegration, insecurity, despair, disillusionment, and problems arising from the capitalist system were prominent in society. These conditions also influenced the literary consciousness of the time, where questions and concerns related to Existentialism gained significance. In Vajpeyi’s poetry, awareness of these circumstances is evident, yet it is accompanied by a strong belief in the inner strength of human beings and the possibilities of life. His poetic vision reflects sensitivity, curiosity, and a deep faith in human values. His poems also reveal a desire to escape from the pressures of crowded, tense, and polluted social surroundings. In this way, his poetic journey contributes a new sense of sensitivity, reflection, and humanistic perspective to modern Hindi poetry.